A Closer Look At WTO's Third Pillar: How WTO Committees Influence Regional Trade Agreements. (3rd October 2018) - McDaniels, Devin; Molina, Ana Cristina; Wijkström, Erik N
Abstract: This paper illustrates how the work of World Trade Organization's (WTO) standing bodies—its 'Third Pillar', as we will call it—is inspiring parties in regional trade agreements (RTA) negotiations and contributing to deeper integration. We focus on the work of the WTO technical barriers to trade (TBT) Committee and explore, as a case study, the extent to which the Committee's decision on principles for development of international standards (the Six Principles ) has shaped provisions in RTAs. This Decision, arguably the most important decision taken by the TBT Committee, is meant to clarify which international standards may be a relevant basis for TBT measures; an issue that has been left undefined under the WTO TBT Agreement. Our analysis covers 260 RTAs, and shows that one quarter of RTAs has sharpened and hardened the Committee's decision by making it directly applicable to Parties (in RTAs) whereas under the WTO they are 'merely' recommendations. A small number of RTAs follow a different approach and explicitly name the sources of relevant international standards.